2013
DOI: 10.1021/jp405473b
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Uranyl(VI) and Plutonyl(VI) Cations in Ionic Liquid/Water Mixtures via Molecular Dynamics Simulations

Abstract: A fundamental understanding of the behavior of actinides in ionic liquids is required to develop advanced separation technologies. Spectroscopic measurements indicate a change in the coordination of uranyl in the hydrophobic ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIM][Tf2N]) as water is added to the system. Molecular dynamics simulations of dilute uranyl (UO2(2+)) and plutonyl (PuO2(2+)) ) solutions in [EMIM][Tf2N]/water mixtures have been performed in order to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 147 publications
3
40
0
Order By: Relevance
“…Soft X-ray spectromicroscopy can also be used to confirm the presence of uranium specifically. Although the oxygen Kedge spectra of uranyl minerals are clearly distinct from the alkali metal complexes used for comparison (Figures 1, 3 and 4), it may be more difficult to distinguish uranyl spectra from that of other heavy metal oxides, such as plutonium, which forms its own plutonyl (PuO 2 2+ ) complexes (Maerzke et al 2013). In practice, the specific presence of uranium can be confirmed by also scanning over the uranium N 5edge at 736.2 eV, an energy that would be accessible by most soft X-ray and STXM beamlines.…”
Section: Resultsmentioning
confidence: 99%
“…Soft X-ray spectromicroscopy can also be used to confirm the presence of uranium specifically. Although the oxygen Kedge spectra of uranyl minerals are clearly distinct from the alkali metal complexes used for comparison (Figures 1, 3 and 4), it may be more difficult to distinguish uranyl spectra from that of other heavy metal oxides, such as plutonium, which forms its own plutonyl (PuO 2 2+ ) complexes (Maerzke et al 2013). In practice, the specific presence of uranium can be confirmed by also scanning over the uranium N 5edge at 736.2 eV, an energy that would be accessible by most soft X-ray and STXM beamlines.…”
Section: Resultsmentioning
confidence: 99%
“…All these simulation results indicate a gradual change of the local ionic coordination environment from IL-rich to waterconcentrated mixtures as more water molecules are introduced into [P 6,6,6,14 ][BOB] IL/water mixtures, akin to a distinct dynamic quantities of ionic species in binary mixtures consisting of imidazolium-based ILs and small molecule solvents (water, methanol, ethanol, etc.). 11,20,37,38,51,61 Translational Diffusion. For a liquid or mixture under thermodynamic equilibrium conditions, the thermal agitation causes translational motion of liquid molecules, which is called self-diffusivity.…”
Section: Methodsmentioning
confidence: 99%
“…An extensive discussion of the resulting effects can be found in recent reviews 16,28 . The outcomes of most studies revealed that low water concentrations induce the formation of residual water states in the IL 9,18 . Further studies highlighted that water molecules accumulate around the hydrophobic parts of the ions with a strong affinity towards the anions 29,30 .…”
Section: Introductionmentioning
confidence: 99%